Evaluating the Utility and Prevalence of HPV Biomarkers in Oral Rinses and Serology for HPV-related Oropharyngeal Cancer - D'Souza, Gypsyamber (Cancer Prev Res (Phila), 2019)
Performance of commercially available human papillomavirus (HPV) assays (approved for cervical HPV detection) is unknown for detecting HPV-related oropharyngeal cancer (HPV-OPC). Assays for detection of HPV DNA [ELISA (DEIA) and Cobas], and RNA (Aptima) in oral rinse samples, and serum HPV oncogene antibodies were evaluated. Sensitivity and specificity of each test was explored among HPV-OPC cases and controls. Biomarker prevalence was evaluated among 294 "at-risk" people (screening) and 133 "high-risk" people [known to previously have oral oncogenic HPV (oncHPV) DNA and/or HPV16 E6/E7 antibodies detected]. HPV16 E6 antibodies had the best overall test performance with sensitivity of 88%, compared with oral HPV16 DNA sensitivity of 51% by DEIA and 43% by Cobas (each P < 0.001). Specificity was comparable in each of these tests (≥98%). When positivity for any oncHPV type was compared with HPV16 for the same test, sensitivity was comparable (60% vs. 51%, 40% vs. 43%, and 92% vs. 88% for DEIA, Cobas, and E6 antibodies, respectively), but specificity was reduced (93%–97%). Aptima had poor sensitivity (23%). Sensitivity decreased when cotesting HPV16 oral rinse DNA and E6 antibodies (37%–48%), or multiple E antibodies (69%–72%). HPV16 DNA were detected in ~2% of the at-risk by either DEIA or Cobas and up to 15% of the high-risk population. HPV16 E6 seroprevalence was 2.3% and 2.4% in the at-risk and high-risk populations, respectively. Oral rinse HPV testing had moderate-to-poor sensitivity for HPV-OPC, suggesting many true positives would be missed in a potential screening scenario. HPV16 E6 serum antibody was the most promising biomarker evaluated.